Percutaneous Radiofrequency Ablation Combined With Chemotherapy Versus Chemotherapy Only for Ovarian Cancer Liver Metastasis - Wu, Chun-Xue; Chen, Miao-Ling; Zhang, Hao; Han, Jian-Jun (Frontiers in Oncology, 2022)
Purpose To compare the feasibility and efficacy of radiofrequency ablation (RFA) combined with chemotherapy and chemotherapy alone in patients with ovarian cancer liver metastasis (OCLM). Methods In this retrospective study, a total of 60 patients diagnosed with OCLM between May 2015 to February 2017 were included. All patients with ovarian cancer received chemotherapy and primary cytoreductive surgery before. Thirty patients underwent RFA and chemotherapy, and thirty patients only took chemotherapy. The overall survival (OS), CA-125 levels, and serum AST and ALT levels were compared between the two groups. Results In the RFA group, the 1-,2-, and 3-year OS rates after RFA were 93.3%, 80.0%, and 53.3%, respectively. Serum AST and ALT levels were both elevated after RFA (p=0.0004, p<0.0001). In the chemotherapy group, the 1-,2-, and 3-year OS rates were 79.5%, 60.1%, and 42.1%, respectively. Levels of serum AST and ALT were stable. CA-125 levels for both groups were also available. Conclusion Based on our analysis of a single institution’s series of patients with OCLM, RFA could be a feasibly effective option in the management of OCLM.